Better Disease Control by Multidrug Regimen in Scabies: A Randomized Controlled Trial - Pandey, Prajwal; Agrawal, Sudha (Nepal Journal of Dermatology, Venereology & Leprology, 2022)
Introduction: Scabies is a highly resilient condition with varying morbidity worldwide. The treatment options widely used for the disease include topical permethrin 5% and oral Ivermectin with similar efficacy. Treatment failure due to non-compliance is a major problem with the current treatment modalities. Objectives: This study was designed to compare the efficacy of combination to the gold standard treatment regimen of scabies. Materials and Methods: A randomized controlled trial was done with 212 patients, divided randomly into two groups Group 1 and Group 2. Group 1 were treated with two-time application of 5% permethrin one week apart while Group 2 were treated with a combination of 5% permethrin and oral ivermectin (200μg/kg) on a single day. Patients were followed up every week for 4 weeks to assess the efficacy and adverse events. Results: The treatment efficacy in group 2 was more compared to group 1 after 2 weeks of follow up (72.6% vs 65.1% after 1 week; 89.6% vs 80.2% after 2 week) however it was not statistically significant. After 4 weeks of follow up, the treatment efficacy in both the groups was similar. The reduction in intensity of itching was almost similar in both the groups at every follow up. Conclusion: The combination of 5% topical permethrin and oral ivermectin showed earlier resolution of clinical symptoms compared to 5% topical permethrin alone repeated in 1 week. The reduction in intensity of itch was similar in both the groups.